Mapping a tradition: francophone women's writing from Guadeloupe - Haigh, Sam (1995)
This thesis is an attempt to contribute to the growing body of work on literature from the French départements d'outre-mer of Guadeloupe and Martinique. More particularly, it represents an attempt to contribute to the growing body of work on women writers from these islands – referred to here as the Antilles - and to situate recent women's writing in relation to the Antillean literary tradition as a whole. The development of this tradition is traced in the introduction to the thesis: from the French colonial writing of the seventeenth and eighteenth centuries, to writing by white, Antillean-born 'creoles' (or békés), and the early 'assimilationist' writing of mulattoes and black Antilleans; from the radical philosophical and poetic texts of négritude, to more sophisticated, recent attempts to find ways in which to imagine Antillean identity and history. It is in relation to the more recent, black Antillean literary tradition, a tradition which has typically excluded Antillean women and Antillean women's writing, that selected novels by Guadeloupean women are examined here. This thesis traces the ways in which these writers position themselves - explicitly and implicitly - vis-à-vis the androcentric tradition which they have inherited. With reference to various feminist theoretical frameworks, it explores also the ways in which women writers disrupt the very tradition which they evoke, bringing questions of gender and sexuality to bear upon those of race. Chapter one examines three early examples of the way in which Antillean women writers interrogate the presuppositions of seminal Antillean texts, as Michèle Lacrosil's Sapotille ou le serein d'argile (1960), her Cajou (1961), and Jacqueline Manicom's Mon Examen de blanc (1972) are set against Fanon's Peau noire,masques blancs. Similarly, the second chapter examines the first two novels of the most prolific Guadeloupean woman writer, Maryse Condé: Heremakhonon (1976) and Une Saison à Rihata (1981). Here, Condé’s interrogation of négritude is explored, as are her efforts to imagine a role for women within a discourse which can be seen to be premised upon the exclusion of 'woman'. Chapter three - in which Simone Schwarz-Bart's Ti Jean L'horizon (1979) and Condé's Les Derniers rois mages (1992) are explored - deals with the way in which the Antillean quest for self-definition centres upon issues of legitimacy and paternity. In this chapter, as in chapter four, the importance of rewriting colonial history via the medium of fiction is examined. In chapter four, aspects of Edouard Glissant's Le Discours antillais are set in relation to Lacrosil's Demain Jab-Herma (1967) and Condé's Traversée de la mangrove (1989). Finally, Condé's Moi. Tituba, sorciere ... noire de Salem (1986) and Dany Bébel-Gisler's Leonora, L'histoire enfouie de la Guadeloupe (1985) are examined as examples of the Antillean movement towards the créolité recently theorised by Jean Bernabé, Patrick Chamoiseau and Raphaël Confiant, as well as towards the Creole language. What emerges throughout these chapters is a sense both of the way in which the Antillean literary tradition is developing and, more importantly, of the way in which Antillean women writers have come to play a crucial role in that development. What also emerges - and this is perfectly exemplified by Condé's very recent La Migration des coeurs (1995), which is discussed briefly in the afterword to this thesis - is the way in which the work of Antillean women writers has come to provide a vital mode of intervention into a tradition from which it had hitherto been excluded.